The making of healthy and moral snacks: A multimodal critical discourse analysis of corporate storytelling. (December 2019) - Chen, Ariel; Eriksson, Göran
Highlights: Moral discourse is used as a marketing tool for contemporary healthy snack companies. Business is recontextualised as family, friendly and authentic relationship. Claimed health qualities are abstract, symbolic and commercialized. Corporate stories attract consumers with 'do good' and 'feel good' myth. Corporate stories can mislead consumers to consume less healthy food. Abstract: This paper examines how snack brands represent themselves as producers of healthy food through corporate stories on their websites. The increased emphasis on health in "the new public health era" has created a market for products promoted as healthy or with some kind of wellbeing association. Riding on this trend, many companies have emerged and positioned themselves as providing good food options. Employing the theory of social semiotics and using multimodal critical discourse analysis, we ask the following questions: How do these companies use corporate stories to make themselves appear as a better alternative than their competitors? How do they make their products appear healthy and attractive to consumers? And how can this kind of marketing help consumers choose healthier products? The analysis of 22 corporate stories of healthy snack companies shows that healthy eating is colonized by a moral discourse for marketing and branding purposes. Furthermore, the health qualities these companies claim to have are abstract, symbolic, and commercialized. We argue that these corporate stories provide no meaningful indication as to the healthiness of these products and can mislead consumers to consume less healthy food while having the intention to eat healthily.